1991
DOI: 10.1002/bem.2250120503
|View full text |Cite
|
Sign up to set email alerts
|

Cancer promotion in a mouse‐skin model by a 60‐Hz magnetic field: II. Tumor development and immune response

Abstract: This paper describes preliminary findings on the influence of 60-Hz (2-mT) magnetic fields on tumor promotion and co-promotion in the skins of mice. The effect of magnetic fields on natural killer (NK) cell activity in spleen and blood was also examined. Groups of 32 juvenile female mice were exposed to the magnetic field as described in part I. The dorsal skin of all animals was treated with a subthreshold dose of the carcinogen 7,12-dimethyl-benz(a)anthracene (DMBA). One week after the treatment, two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 47 publications
2
37
1
1
Order By: Relevance
“…The promotion experiment, using the SENCAR mouse, employed DMBA (2.56 pg) as initiator and chronic exposure (6 hr/day, 5 days/week) to 60-Hz, 2-mT continuous fields. Results were negative, confirming previous similar reports (58,59 130 ,uT, each applied in succession for 20 min followed by a 2-hr pause).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The promotion experiment, using the SENCAR mouse, employed DMBA (2.56 pg) as initiator and chronic exposure (6 hr/day, 5 days/week) to 60-Hz, 2-mT continuous fields. Results were negative, confirming previous similar reports (58,59 130 ,uT, each applied in succession for 20 min followed by a 2-hr pause).…”
Section: Resultssupporting
confidence: 89%
“…These include four pairs of lifetime or multigeneration exposure studies [(11-13) vs (16), (11-13) vs (14), (11)(12)(13) vs (15), and (14) vs (16)]; four pairs of studies using the rat mammary carcinoma promotion model [(29) vs (28), (32,38) vs (25)(26)(27), (33)(34)(35) vs (25,26,32,38), and (33,34) (the second 13-week study) vs (33,35) (the 26-week study)]; three pairs of studies using the mouse skin promotion/co-promotion model [(54) vs (58,59), (50) As shown in Table 6, aspects of the comprehensive 2-year chronic bioassay conducted by the NTP (11-13) overlap three independently conducted long-term chronic bioassays (14)(15)(16), and two of the latter three studies also have overlapping aspects (14,16 (28), (32,38) vs (25)(26)(27), and (33,34) (the second 13-week study) vs (33,35)…”
Section: Discussionmentioning
confidence: 99%
“…Lyle et a1.32~ reported the suppression of T-lymphocyte cytotoxicity following exposure to weak EMF. Further, McLean et al 33' noted a decrease in the activity of natural killer cells in mice exposed to both 7, 12-dimethylbenz(a)anthracene (DBMA), a carcinogen, and to 60 Hz EMF. Cossarizza et al 34' found that ELF pulsed EMF increased cell proliferation in lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A difference in the cumulated number of mice with tumors was observed, but this difference did not reach statistical significance at the end of the observation period (23 weeks). Splenomegaly (11) was observed among the TPA+ magnetic field-exposed mice, and there was a greater number of mononuclear cells in the spleens of animals with combined exposure. There was also a depressed NK cell activity.…”
Section: Interacdon Studiesmentioning
confidence: 92%